Polymorphisms in the IL17A gene do not influence the clinical, laboratory and radiological manifestations of tuberculosis (Research, Society and Development, 2022)
Some single-base polymorphisms (SNPs) in cytokine genes have the potential to affect gene expression and/or biological activity of the respective cytokine, and there is evidence of the association of different SNPs with tuberculosis in several different populations. Studies involving the influence of SNPs on the IL17A gene are still controversial, behaving differently among different populations. Thus, research into the association of SNPs in the IL17A gene with the clinical course of the disease may contribute to a better understanding of TB susceptibility and development. Therefore, the aim of the present study was to evaluate the influence of SNPs on the IL17A gene and their clinical-laboratory association in patients with tuberculosis. Therefore, 35 patients with tuberculosis and 26 controls were studied. The evaluation of the SNPs in the IL17A gene, rs7747909 and rs2275913, was performed using the allelic discrimination technique by real-time PCR. Clinical, laboratory and radiological data were obtained by collecting medical records. Analyzes were performed using Fisher's test, considering significant values ​​p